A bi-objective model for the integrated frequency-timetabling problem - Avila Torres, Paulina Alejandra; Lopez Irarragorri, Fernando; Caballero Fernandez, Rafael (Wit Press, 2014)
The urban transport planning process has four basic activities: network design, timetable construction, vehicle scheduling and crew scheduling. In this work we focus on the urban bus timetable construction problem which has two sub-activities: bus frequency calculation and bus departures setting. Typically, these sub-activities are done sequentially, which has some drawbacks: to overcome these drawback we propose to integrate both these sub-activities. We take into consideration: multiple planning periods, synchronizations events (a synchronization occurs when two buses from different routes arrive to a node within a time window), fixed and variable operations costs and uncertain demand in each period.